ANALISIS EFEKTIVITAS MODEL PEMBELAJARAN DALAM MENINGKATKAN PEMAHAMAN KONSEP SISWA PADA PELAJARAN IPA SMP NEGERI 1 TUHEMBERUA - GEA, SEPI FITA SARI; WARUWU, TOROZIDUHU; ZEGA, NOVELINA ANDRIANI; WARUWU, YAREDI (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2025)
ABSTRACT This research was motivated by students who were not actively involved in learning, teachers who still used lecture learning methods, and students' lack of understanding of concepts in learning. The type of research used is a qualitative descriptive approach. The research location is at SMP Negeri 1 Tuhemberua. The research population is class IX students in the odd semester of the 2024/2025 academic year. Research instruments, namely: observation sheet on the effectiveness of the learning model, observation sheet on understanding concepts, and learning outcomes tests. Research results: (1) The effectiveness of the learning model in science learning at SMP Negeri 1 Tuhemberua was discovered that at Meeting 1 the percentage was 66.91% with "sufficient" criteria, at Meeting 2 the percentage was 78.41% with "good" criteria, and at Meeting 3 the percentage was 84. .09% with "good" criteria, so the average percentage of effectiveness of learning models in science learning is 76.14% with "good" criteria. (2) The students' ability to understand concepts in science learning was found at Meeting 1, the average percentage was 71.42% with the "sufficient" criteria, Meeting 2 obtained an average percentage of 75.62% with the "good" criteria, and Meeting 3 the average percentage was obtained. -The average percentage is 82.62% with "good" criteria, so the average percentage of students' conceptual understanding ability is 76.55% with "good" criteria. (3) Student learning outcomes in science learning obtained an average score of 80.15 with good criteria, and the percentage of students who completed their studies was 81.48% while the percentage who did not complete their studies was 18.52%. ABSTRAK Penelitian ini dilatarbelakangi oleh siswa yang kurang terlibat aktif dalam pembelajaran, guru yang masih menggunakan metode pembelajaran ceramah, dan kurangnya pemahaman konsep siswa dalam pembelajaran. Jenis penelitian yang digunakan adalah pendekatan deskriptif kualitatif. Lokasi penelitian yaitu di SMP Negeri 1 Tuhemberua. Populasi penelitian yaitu siswa kelas IX semester ganjil Tahun Pelajaran 2024/2025. Instrumen penelitian, yaitu: lembar observasi efektivitas model pembelajaran, lembar observasi pemahaman konsep, dan tes hasil belajar. Hasil penelitian: (1) Efektivitas model pembelajaran pada pembelajaran IPA di SMP Negeri 1 Tuhemberua diketahui pada Pertemuan 1 diperoleh persentasenya sebesar 66,91% dengan kriteria “cukup”, Pertemuan 2 diperoleh persentasenya sebesar 78,41% dengan kriteria “baik”, dan Pertemuan 3 diperoleh persentasenya sebesar 84,09% dengan kriteria “baik”, sehingga rata-rata persentase efektivitas model pembelajaran pada pembelajaran IPA sebesar 76,14% dengan kriteria “baik”. (2) Kemampuan pemahaman konsep siswa pada pembelajaran IPA diketahui pada Pertemuan 1 diperoleh rata-rata persentasenya sebesar 71,42% dengan kriteria “cukup”, Pertemuan 2 diperoleh rata-rata persentasenya sebesar 75,62% dengan kriteria “baik”, dan Pertemuan 3 diperoleh rata-rata persentasenya sebesar 82,62% dengan kriteria “baik”, sehingga rata-rata persentase kemampuan pemahaman konsep siswa sebesar 76,55% dengan kriteria “baik”. (3) Hasil belajar siswa pada pembelajaran IPA diperoleh nilai rata-ratanya sebesar 80,15 dengan kriteria baik, dan pesersentase siswa yang tuntas belajar sebesar 81,48% sedangkan persentase yang tidak tuntas belajar sebesar 18,52%.